Identification of Novel Growth Regulators in Plant Populations Expressing Random Peptides. Issue 2 (14th August 2017) - Bao, Zhilong; Clancy, Maureen A.; Carvalho, Raquel F.; Elliott, Kiona; Folta, Kevin M.
Abstract : New peptide-based plant growth regulators may be identified by screening populations of plants with random peptide sequences that cause reproducible effects on biology, including plant growth inhibition, aberrant light response, and hastened developmental transitions. Abstract: The use of chemical genomics approaches allows the identification of small molecules that integrate into biological systems, thereby changing discrete processes that influence growth, development, or metabolism. Libraries of chemicals are applied to living systems, and changes in phenotype are observed, potentially leading to the identification of new growth regulators. This work describes an approach that is the nexus of chemical genomics and synthetic biology. Here, each plant in an extensive population synthesizes a unique small peptide arising from a transgene composed of a randomized nucleic acid sequence core flanked by translational start, stop, and cysteine-encoding (for disulfide cyclization) sequences. Ten and 16 amino acid sequences, bearing a core of six and 12 random amino acids, have been synthesized in Arabidopsis ( Arabidopsis thaliana ) plants. Populations were screened for phenotypes from the seedling stage through senescence. Dozens of phenotypes were observed in over 2, 000 plants analyzed. Ten conspicuous phenotypes were verified through separate transformation and analysis of multiple independent lines. The results indicate that these populations contain sequences that often influence discrete aspects of plant biology. Novel peptides that affect photosynthesis, flowering, and red light response are described. The challenge now is to identify the mechanistic integrations of these peptides into biochemical processes. These populations serve as a new tool to identify small molecules that modulate discrete plant functions that could be produced later in transgenic plants or potentially applied exogenously to impart their effects. These findings could usher in a new generation of agricultural growth regulators, herbicides, or defense compounds.